BANGUNAN ARGUMENTASI YANG MENEMPATKAN ALAM SEBAGAI SUBJEK HUKUM - Melliana , Ayu Okta; Wauran, Indirani (Universitas Kristen Satya Wacana, 2023)
This study examines nature as a legal subject in Indonesian civil law. So far, humans have been colonized by the ethics of anthropocentrism, which considers nature as an object, so human behaviour tends to be arbitrary and detrimental to the preservation of nature. As a critique of the concept of anthropocentrism, the concept of ecocentrism emerged, which views nature as having sovereignty. So, with the concept of ecocracy, nature can increase from object to subject. This research method compares the natural (environmental) protection regulation in Indonesia with other countries that have recognized nature as a legal subject. Based on the results of the study, there are limitations to the regulation of nature protection in Indonesia and placing nature as a legal subject provides legal implications, namely changes in regulations that place more emphasis on natural rights, the need for a guardian for nature in carrying out legal actions and the addition of legal standing for nature in civil law.